Determination of Teachers Readiness in Implementing Curriculum 2013 at Senior High Schools in Kupang City, East Nusa Tenggara - Sakan, Rola Marlince; Utanto, Yuli; Rifai RC, Achmad (Universitas Negeri Semarang, 2019)
This study aims to analyze the effect of teacher training, teacher competence and school facility and infrastructure partially and simultaneously to teacher readiness in implementing Curriculum 2013 at Public Senior High School (SMAN) in Kupang city, East Nusa Tenggara. The study included qualitative research using ex post facto design approach and used proportional cluster random sampling technique to collect the subjects. Total subjects in this research were 169 teachers from 807 teachers as research population at senior high school in Kupang city, East Nusa Tenggara. The technique of collecting data used questionnaire and Likert scale was applied in measuring each variable. The analysis method employed multiple linear regression analysis and applied for the SPSS program. The results of this research are: (1) The quantity of the effect of teacher training to teacher readiness in implementing Curriculum 2013 was 30.20%, (2) Teachers competence to teacher readiness in implementing Curriculum 2013 was 47.40%, (3) The quantity of the effect of facilities and infrastructure to teacher readiness in implementing Curriculum 2013 was 17.20%. Teacher training, teacher competence and facilities and infrastructure to teacher readiness in simultaneously in implementing Curriculum 2013 in public school of senior high schools in Kupang city, East Nusa Tenggara was 63.50% and remaining 36.50%were influenced by other factors. Teacher training, teacher competence, and facility and infrastructure have a positive and significant effect on teacher readiness in implementing Curriculum 2013 at senior high schools in Kupang city, East Nusa Tenggara.